Comparison of man hours utilized for mandibluar overdenture treatment retained by single implant with bar fabricated by CAD-CAM process and conventional casting processs - An Vivo study - Amit Patil; Prashanti Adsare; Pooja Raj; Shivakumar Puranik; Koineni Rajender; Rajesh Menga (Wolters Kluwer Medknow Publications, 2024)
Introduction: Both the population's average life expectancy and the number of patients without teeth are rising. A 2012 epidemiological survey in India found that 30% of the population is edentulous. The rehabilitation process with a set of removable maxillary and mandibular complete dentures is the standard treatment for patients who are edentulous. This study is the first to incorporate and compare a novel approach to a single implant-retained mandibular overdenture with a bar attachment fabricated by CAD-CAM and a casting process on a single implant in the symphysis region. Method: Five maxillary and mandibular completely edentulous patients were enrolled in the study. Results: Significant difference was seen in the conventional laboratory time and CAD-CAM time as P < 0.05. Conclusion: Compared to the conventional casting process, the single implant-supported bar mandibular overdenture (SISBOD) with a novel bar required fewer man hours and was more convenient.